Illiteracy, ill-literacy and literacy among Western Armenians: En route from the Near East to the West, from the 1950s until today - Hervé Georgelin (European Journal of Turkish Studies)
Based on observations of a post-Ottoman Armenian family and their network of relatives and friends made over more than fifteen years, this article scrutinizes the switch from an almost exclusively oral to a predominantly written world of perception, expression, and communication. Far from being solely an impediment to social life in the Western world, social and cognitive skills acquired in the Ottoman popular culture and inherited by the family's new generations proved helpful in new places and new settings. Though changes occur over generations, these are relatively slow and are still in progress. The common Ottoman Armenian heritage, including the Armenian language still link together a group of relatives scattered over three continents, be it in a frail way.